Field Works of Caesarians and Pompeians at Dyrrachium (48 BCE) - Wilczyński, Michał (Tools of War, 2023)
During the campaigns of the Gallic War and the Civil War, Gaius Julius Caesar repeatedly led siege operations, personally commanding at least 17 sieges. Caesar repeatedly demonstrated innovation during them, the most famous example of which is the construction of a double line of fortifications around Alesia in 52 BCE, which allowed the Romans to repel the attacks of both the Gallic relief and the besieged. Siege operations undertaken by Caesar at Dyrrachium in 48 BC, to which this article is devoted, seems no less interesting. At that time, he showed particular creativity and boldness by surrounding the more numerous army of Gnaeus Pompey the Great with a belt of fortifications some 25 km long. The article analyses the following issues: the topography of the battle site; reasons for initiating the fortification effort by Caesar; types of fortifications erected by his soldiers; the fortification works carried out by the Pompeians and their actions to slow down the enemy's work; the factors enabling Pompey's army to break the blockade. In the conclusion, assessments of Caesar's undertaking were presented, and an attempt to answer the question about the uniqueness of the activities carried out under Dyrrachium from the point of view of the ancient art of war was made. The source basis for the analysis is the account of Book III of Caesar's Commentarii de bello civili (BC III, 41–54; 58–72), supplemented by the accounts of other ancient authors.